2018
DOI: 10.22319/rmcp.v9i4.4468
|View full text |Cite
|
Sign up to set email alerts
|

Uso de nisina y quitosano para la inhibición de Staphylococcus aureus resistente a antibióticos y asociado a mastitis bovina

Abstract: En este trabajo se describen los patrones de resistencia a antibióticos de aislados de Staphylococcus aureus obtenidos de vacas con mastitis, así como su susceptibilidad in vitro a nisina, quitosano y al compósito nisina/quitosano. A partir de muestras de leche obtenidas de vacas enfermas se aislaron e identificaron 53 S. aureus, a los cuales se les analizó el perfil de resistencia a antibióticos. Los resultados evidenciaron una alta frecuencia de resistencia hacia el grupo de los beta-lactámicos, principalmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…In addition, it was noted that 10% (n=5) showed intermediate resistance. Jiménez et al [9] in their investigation of resistance profiles by Staphylococcus aureus against 10 µg ampicillin, they obtained 81.5% sensitivity and 18.5% resistance, Sánchez et al [29] of a total of 53 isolates, 60.3% (n=32) presented resistance to 10 µg ampicillin, this interaction being one of those with the highest resistance rates, Guzmán et al [8] of 32 isolates observed that 86.6% presented resistance to 10 µg ampicillin, observing that when molecularly analyzing mentioned isolates, 100% presented the blaZ gene and 36.6% were positive for the mecA gene, and it is strongly linked to the phenotypic and genotypic presentation of resistance to penicillins and beta-lactams by the bacteria under study since it gives it the ability to generate beta-lactamases that inhibit the mechanism of action of beta-lactam drugs.…”
Section: Antimicrobial Susceptibility Of Ampicillin Against Staphyloc...mentioning
confidence: 99%
“…In addition, it was noted that 10% (n=5) showed intermediate resistance. Jiménez et al [9] in their investigation of resistance profiles by Staphylococcus aureus against 10 µg ampicillin, they obtained 81.5% sensitivity and 18.5% resistance, Sánchez et al [29] of a total of 53 isolates, 60.3% (n=32) presented resistance to 10 µg ampicillin, this interaction being one of those with the highest resistance rates, Guzmán et al [8] of 32 isolates observed that 86.6% presented resistance to 10 µg ampicillin, observing that when molecularly analyzing mentioned isolates, 100% presented the blaZ gene and 36.6% were positive for the mecA gene, and it is strongly linked to the phenotypic and genotypic presentation of resistance to penicillins and beta-lactams by the bacteria under study since it gives it the ability to generate beta-lactamases that inhibit the mechanism of action of beta-lactam drugs.…”
Section: Antimicrobial Susceptibility Of Ampicillin Against Staphyloc...mentioning
confidence: 99%
“…El uso del quitosano como suplemento alimenticio podría tener un efecto positivo en animales de granja, ya que, debido a sus propiedades bioactivas éste puede interactuar con la microbiota intestinal, favorecer la utilización de energía, y en consecuencia las variables productivas en corral, como la ganancia de peso y el índice de conversión alimentaria (7,8,9) . Adicionalmente, cabe mencionar que el proceso de extracción y obtención del quitosano representa un bajo costo, lo cual puede favorecer la rentabilidad de las granjas avícolas (10) .…”
unclassified